Using pyrene to probe the effects of poloxamer stabilisers on internal lipid microenvironments in solid lipid nanoparticles. Issue 12 (26th October 2020) - Taylor, Jessica M.; Scale, Kyle; Arrowsmith, Sarah; Sharp, Andy; Flynn, Sean; Rannard, Steve; McDonald, Tom O.
Abstract : Pyrene can be used to investigate the internal polarity inside solid lipid nanoparticles; small changes in the structure of the poloxamer surfactants can influence the polarity inside the core. Abstract : Solid lipid nanoparticles (SLNs) have proved to be effective nanocarriers with many advantages over other non-lipid-based systems. The development of new SLN formulations is often hindered through poor drug loading capacity and time-consuming optimisation of lipid/stabiliser combinations. One challenge in the development of new SLN formulations is understanding the complex interactions between amphiphilic stabilisers and hydrophobic lipids; the nature of these interactions can significantly impact SLN properties, including the internal polarity within the nanoparticle core. Herein, we report the use of pyrene to probe the internal lipid microenvironment inside SLNs. We investigate the effect of using different poloxamer stabilisers on the internal polarity of SLNs formed using the common solid lipid, Compritol 888 ATO. We show that the polarity of the internal lipid environment is modified by the length of the poly(propylene oxide) (PPO) block of the poloxamer stabiliser, with longer PPO blocks producing SLNs with less polar lipid cores. Blending of stabilisers could also be used to tune the polarity of the core lipid environment, which may allow for adjusting the polarity of the lipid to assist the loading of different therapeutics.